Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Keamanan Layanan Face Recognition Terhadap Kepercayaan Penumpang Kereta Api Indonesia di Stasiun Malang - Yesy Putri Winarni; Lina Budiarti; Rena Feri Wijayanti (Indo Publishing, 2026)
PT Kereta Api Indonesia (Persero) is one of the modes of mass transportation that is in great demand by the Indonesian people. Along with the development of digital technology, PT Kereta Api Indonesia (Persero) implements face recognition boarding gate services at various major stations to efficiency and improve the safety of the passenger boarding process. This study was a quantitative research with variables of ease of use perception, service safety perception, and passenger trust. The data collection technique in this study was carried out through the distribution of questionnaires directly to 100 respondents who were train passengers using the face recognition boarding gate service at Malang Station. The results of the multiple linear regression analysis showed that Fcount > Ftable, which is 48,603> 3.09, with a significance value of 0.000 < 0.05.The coefficient of determination (R²) was 0.501 (50%). This indicating that the variables of perceived ease of use and service security simultaneously explained 50% of the variance in passenger trust, while the remaining 50% was influenced by other factors not examined in this study. Therefore, H₀ was rejected and H₃ was accepted, indicating that perceived ease of use (X₁) and perceived service security (X₂) simultaneously have a significant effect on passenger trust (Y). Based on the findings of this study, it can be concluded that PT Kereta Api Indonesia (Persero) can strengthen passengers trust in the face recognition boarding gate service by maintaining its ease of use while continuously improving service security. As a result, passengers are expected to have greater confidence in using the service at Malang Station. PT Kereta Api Indonesia (Persero) is recommended to maintain the ease of use of the face recognition service by providing clear instructions and assistance for first-time users, while ensuring consistent service procedures and reliable system performance to strengthen passengers' trust in the service..